Preservation Of Local Traditions As An Effort To Strengthen The Character Of Citizen Social Care (Case Study Of Basalwir Tradition In Dofa Village, Sula Islands) - Sapsuha, Karti; Noe, Wahyudin; Abbas, Irwan; Nurfan, Roy (Universitas Negeri Gorontalo, 2024)
Basalwir is a tradition of cooperation of the Sula tribe in every celebration event, whether it is a wedding, circumcision, tasyakuran departure of Hajj, or Italian, to foster the social care character of the community. However, this tradition has experienced a shift in value and meaning due to the modern lifestyle of the community, who tend to carry out celebrations practically and economically, such as using catering services. This research aims to describe the efforts of the people of Dofa Village, West Mangoli District, Sula Islands Regency, North Maluku Province, in preserving the Basalwir tradition as an effort to strengthen the social care character of citizens. This research is qualitative research with an ethnographic study method. The results illustrate that most of the Dofa community still preserves the Basalwir tradition, but its existence is starting to be threatened by changes in people's behavior that follow modern lifestyles. The values contained in Basalwir are togetherness, unity, and responsibility, which can shape citizens' social care character and strengthen the bonds of brotherhood of the Dofa village community. Supporting factors for the preservation of the Basalwir tradition because: a) the support and commitment of the community in maintaining the Basalwir tradition, and b) the enactment of customary laws that residents still uphold. The inhibiting factor in preserving the Basalwir tradition is the need for greater public awareness of its values and meanings as local community wisdom.